STRATEGI KOMUNIKASI HUMAS POLRES BOGOR SEBAGAI LAYANAN INFORMASI MELALUI MEDIA SOSIAL INSTAGRAM (Jurnal Ilmu Komunikasi, 2024)
Public Relations of Bogor Police has an important role in conveying information to the public quickly and precisely through Instagram social media @humaspolresbogor. This research discusses the communication strategy of the Bogor Police Public Relations as an information service through Instagram social media. The purpose of this research is to find out how the communication strategy of the Bogor Police Public Relations in conveying information to the public through Instagram social media. This research uses a qualitative approach with a constructivism paradigm to get a picture of the views of a person under study by determining informants using purposive techniques, this research data collection is obtained through observation, interviews, and documentation. This research uses Cutlip, Center, and Broom Theory, namely: Data collection, planning, action and communication, and evaluation. The results showed that the Bogor Police Public Relations Strategy in conveying information to the public through Instagram social media by uploading content regularly, utilizing existing features on Instagram such as Reels, Instastory, and DM. The content uploaded by the Public Relations of Polres Bogor includes  police activities, information needed by the community, and news of arrests. The content is made as attractive as possible by using templates and choosing words that are easily understood by various groups.